The Influence of Product Quality, Brand Image, and Lifestyle on the Decision to Purchase iPhone 12 among BRI Bank Employees at the Jakarta Region I Office - Muhammad Ilham (Journal of Social Research, 2023)
This study aims to test and prove the effect of Product Quality, Brand Image, and Lifestyle on the decision to purchase an iPhone 12 for Bank BRI employees in the Jakarta Regional Office I. The sampling technique used is nonprobability, namely convenience sampling. The research respondents used were 65 respondents with qualifications, namely employees who work at Bank BRI Regional Office I Jakarta and iPhone 12 users. Data was collected using the digital questionnaire method, namely the Google form. The research method used is the Quantitative Research Method. The analytical method used is PLS (Partial Least Square) with the SmartPLS version 3 program. The results of the study conclude that Product Quality, Brand Image, and Lifestyle have a positive and significant influence on Purchase Decisions.